The effictiveness of corporate identity for event company / Tarmizie Ibrahim - Ibrahim, Tarmizie (Faculty of Architecture, Planning and Surveying, 2013)
Corporate identity for event is the corporate event management that will focus upon the communication and philosophy behind designing for event concept based art and graphic work. The research will particularly look at, discuss, and discover the aesthetic and conceptual formulations for corporate event managing. This thesis offers an included perspective of the theory, applications and implementation of true corporate event design in Malaysian eventmanaging. There are explanations of what corporate event is and the areas chosen forexamination Chapter 1 in this academic writing is focusing the background research of “what is event launching”, the objective of research, “the effectiveness of using corporate identity”, problem statement o f the event launching company, scope o f study, it is going to explain the focus company (TRUevent Sdn. Bhd.) and the problem, significant o f study is focusing the future of event launching and the person who involved in event launching, and the literature review for this topic is explain about the advantages for using corporate identity in event launching. The second chapter, it is focusing the research methodology, there have two data applications, the first one is primary data and the second is secondary data. The third chapter, it is focusing the data analysis and the finding of the effectiveness of corporate identity for event launching, it will explain about the finding of the primary and secondary data also the summarizing of the findings. The last chapter, chapter 4 will summarize the findings in chapter 3 and give the conclusion about the result of using the effectiveness of corporate identity for event launching. This chapter also explains about the recommendation for this topic and the design of event launching that using corporate identity concept/ theme.